Training on Preparation of Simple Financial Statements and Marketing Strategies for Cendol "Men Tablen" - Anggiriawan, I Putu Budi; Jayawarsa, Anak Agung Ketut; Pratama, I Gede Surya (MOVE: Journal of Community Service and Engagement, 2024)
Business in the cendol sector opens up economic opportunities for many housewives to increase their family income. With relatively small capital and flexible working hours, many mothers can get involved in the cendol business as a way to support their family's financial needs. Through community service activities, cendol MSMEs receive education and training that helps them understand and apply modern marketing strategies, so that they can increase their competitiveness and business growth. The first obstacle is limited capital so that the production process is still limited. Second, this group has never made a financial report so that the development of the business or performance of this group cannot be known. Third, the distribution and marketing of products are still carried out conventionally. Partners do not yet have a qualified marketing strategy, resulting in the coverage of the product market share being very minimal. The advancement of digital technology in the era of globalization without being balanced by the ability to utilize advances in science and technology has hampered business development. The conclusion of the implementation of this community service is 1) Cendol Men Tablen UMKM does not yet have adequate financial transaction records, as well as the desire to expand market share, 2) Socialization related to marketing strategies based on Marketing Mix is considered appropriate to the needs of partners, and 3) Cendol Men Tablen UMKM experiences difficulties in meeting the needs of production support facilities due to limited capital.